2021
DOI: 10.1101/2021.06.15.448579
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dietary palmitic acid induces innate immune memory via ceramide production that enhances severity of acute septic shock and clearance of infection

Abstract: Trained immunity is epigenetic reprogramming that occurs in innate immune cells in response to primary inflammatory stimuli and leads to enhanced inflammation upon secondary challenge with homologous or heterologous stimuli. We find exposure to high-fat diets confers a hyper-inflammatory response to systemic LPS and enhanced mortality, independent of microbiome. Ketogenic diet (KD) does not alter homeostatic inflammation, but enhances the response of immune cells to LPS challenge ex vivo. Lipidomics identified… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 92 publications
(154 reference statements)
0
3
0
Order By: Relevance
“…Priming with palmitic acid increases the response to many innate stimuli, including TLR2, TLR4, and dectin-1 agonists. Napier and colleagues have shown that other models of palmitate treatment can augment macrophage inflammation in culture and induce an innate memory-like effect 39 . Moreover, her group showed that dietary palmitate can augment the inflammatory response to endotoxemia and improve the clearance of Candida albicans in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Priming with palmitic acid increases the response to many innate stimuli, including TLR2, TLR4, and dectin-1 agonists. Napier and colleagues have shown that other models of palmitate treatment can augment macrophage inflammation in culture and induce an innate memory-like effect 39 . Moreover, her group showed that dietary palmitate can augment the inflammatory response to endotoxemia and improve the clearance of Candida albicans in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Palmitic acid was chosen as our initial stimulus because it is the most common saturated fatty acid in the human body, is elevated in individuals with obesity due to lipolysis, and it activates TLR4, a receptor that can promote innate immune memory 36 . Additionally, palmitate has been shown to elicit an obese-like adipose macrophage phenotype in bone marrow derived macrophages (BMDM) and priming in other models [37][38][39] . Following 24-hour activation and a 6-day washout, palmitic acid priming increased maximal extracellular acidification rate (ECAR), a proxy for glycolysis, and appeared to increase maximal oxygen consumption rate (OCR), a proxy for oxidative phosphorylation, although this measure was not significant (Figure 2B&C).…”
Section: Palmitic Acid Induces Innate Immune Memory Responses In Bone...mentioning
confidence: 99%
“…Palmitic acid was chosen as our initial stimulus because it is the most common saturated fatty acid in the human body, is elevated in individuals with obesity due to lipolysis, and it activates TLR4, a receptor that can promote innate immune memory (37). Additionally, palmitate has been shown to elicit an obese-like adipose macrophage phenotype in bone marrow derived macrophages (BMDM) and priming in other models (38)(39)(40). Following 24-hour activation and a 6-day washout, palmitic acid priming increased maximal extracellular acidification rate (ECAR), a proxy for glycolysis, and modestly increased maximal oxygen consumption rate (OCR), a proxy for oxidative phosphorylation, although this measure was not significant (Figures 2B, C).…”
Section: Palmitic Acid Induces Innate Immune Memory Responses In Bone...mentioning
confidence: 99%